Geochemistry of Clay Minerals Associated with Phosphates in Akashat Formation (middle Paleocene), Iraqi Western Desert - Al-Youzbakey, Kotayba Tawfiq; Al-Dabbagh, Salim Mahmood (Journal of natural sciences, life and applied sciences, 2023)
Many Trace elements are related to the presence of clay minerals, which are associated with francolite in phosphorites. Although the clay minerals are found in very low concentration, but they explain clearly the distribution of trace elements in phosphatic facies of Akashat Formation in Iraqi western desert. Almost these clays are palykorskite, sepiolite and montmorillonite which are found through the francolite formation in shallow marine environment in the continental shelf. Clays found with phosphate as distracted grains and within the phosphatic grain in fractures or around the cortex in phosooids and phoscortoids. The organic activity and the surface charges on the suspended clay particles play an important role in fixing the clays on phosphatic grains through the formation process or early diagenesis stages. The presence of clay minerals (despite their low percentage) controls the distribution of some trace elements, most of which are adsorbed on clay minerals such as zinc (Zn), nickel (Ni), copper (Cu) and cobalt (Co), while some of them replace the main elements such as rubidium (Rb) instead of potassium (K) and gallium (Ga) instead of aluminum (Al), and other elements are distributed between adsorption on francolite and clay minerals such as vanadium (V), chromium (Cr) and manganese (Mn).